Caracteristics of sunscreen from seaweed porridge (Turbinaria conoides) and galangal extract (Alpinia galangal) - Neneng Sulastri; Dini Surilayani; Ginanjar Pratama; Afifah Nurazizatul Hasanah (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Natural ingredients that have sunscreen activity, namely galangal (Alpinia galanga) have a role in absorbing UV rays. Seaweed (Turbinaria. conoides) contains alkaloids, tannins, antioxidants, fucoxanthin. Many cases of skin damage due to harmful cosmetic ingredients and exposure to UV rays have encouraged the authors to explore the natural wealth of seaweed and galangal into skin care products. The aim of the study was to determine the optimum formulation and evaluate the best characteristics of seaweed and galangal sunscreen cream preparations. This research was experimental with four treatments and three replications giving concentrations of seaweed and galangal F0 (control), F1(1:1), F2(1:2), F3(2:1). The tests carried out included hedonic, homogeneity, centrifugal, viscosity, SPF, humidity and pH tests. The hedonic results show significant differences in color parameters (F3). All treatments produced cream type (O/W) and were homogeneous, there was no phase change in the centrifugal test. The viscosity and pH values meet the requirements and can moisturize, the highest SPF value (F2) is 3.67 in the minimum category. The more addition of seaweed affects the color characteristics. The more galangal added, the higher the SPF. Of all the treatments, the formulation with the addition of seaweed and galangal affected the characteristics of the resulting cream.